Allas and weilawei: Interjections in some of Chaucer’sCanterbury Tales (Fragment III: Wife of Bath, the Friar,the Summoner) - Reber, Elisabeth; Sauer, Hans (2022)
We investigate Chaucer’s use of interjections in Fragment III of the Canterbury Tales, which comprises “The Wife of Bath’s Prologue and Tale”, “The Friar’s Prologue and Tale”, and “The Summoner’s Prologue and Tale”. We discuss the problem of how to distinguish interjections from other word classes, and we distinguish primary interjections such as allas, buf, ey, fy, hayt, lo, weilawei and secondary interjections, such as hayl, look, now, peace, welcome, why. As a third group we also take corroborative phrases such as by God into consideration. We look at the frequency of the various interjections: Now, lo, nay as well as a, by God, and pardee are frequent and occur in all the tales of Fragment III; on the other hand of the frequency scale there are buf, which is a hapax legomenon, and the rarely attested hayt. We describe the interjectional spectrum used in Fragment III based on their functions. Interjections can, for example, serve as indicators of emotions (allas, weilawei), as corroboratives (by God) and expletives (a devel weye), as discourse markers (now thanne), as response forms (nay, ye, yis), as polite speech act formulae (grant mercy, no fors), etc. The paper further offers an analysis of the phonology, morphology, verse meter and stress pattern. As the Middle English vocabulary generally, the etymology of the interjections is mixed: some go back to Old English, especially weilawei, but many were borrowed from French (or ultimately from Latin), e.g., allas, ey, fy, pardee. Chaucer’s characters often use not just one, but two or three interjections in combination, e.g., Allas! and weylawey! or allas nay, nay, mainly probably for additional emphasis. We suggest that that the interjectional spectrum in Fragment III (1) expands on Biber et al’s. (1999) inserts and Culpeper & Kytö’s (2010) pragmatic noise; (2) undergoes change like words; and is indexical (3) of a multi-lingual social context (4) and of oral and literary conventions.
Keywords: Chaucer, Geoffrey